Macro-Econometric Model: Keynesian-Monetarist Synthesis of the International Balance of Payments (The Indonesian Case) - Aris Soelistyo (Universitas Hayam Wuruk Perbanas, 2022)
The study of the Keynesian-monetarist synthesis macroeconomic model on Indonesia’s balance of payments combines the goods market and money market approaches to Indonesia’s balance of payments theory. This study used three models of shortness to balance payments: Keynesian, monetarism, and synthesis of Keynesian and monetarism methods. Data was used from 1998 to 2019 from International Monetary Fund, international financial statistics, and balance sheet book from Bank Indonesia statistics report. The data is analyzed using reduced-form regression analysis. The results show that based on the monetarist approach to the balance of payments, it is found that the effect of the money multiplier on the international balance of payments; the magnitude of which is strongly influenced by the size of the high-powered money or the monetary base; has a negative effect on the international balance of payments, while the Net Domestic Assets has a positive effect on the international balance of payments. In the Keynesian model of the international balance of payments, it is found that government spending, world income, and domestic prices have a negative effect on Indonesia’s balance of payments. Based on the Keynesian-monetary syntheses approach to the balance of payments, it is found that government spending and domestic prices have a negative effect on the international balance of payments; the higher the level of government spending and the level of domestic prices will reduce foreign exchange reserves. At the same time, an increase in foreign income, in this case, an increase in US GDP, will increase Indonesia’s foreign exchange reserves.